The Validitas Empiris dan Reliabilitas Instrumen Penilaian Literasi Sains Berdasarkan Buku Pengayaan Fisika Angin Puting Beliung - Venny Mulyana; Desnita Desnita (Jurnal Penelitian Pendidikan IPA, 2023)
Scientific literacy is one of the most important skills and should be strengthened by students. Students with scientific literacy skills will be able to apply the knowledge learned to solve problems in their everyday lives. This study aims to disclose the empirical validity and reliability of the scientific literacy assessment instrument. It is necessary to use an assessment tool that can measure all aspects of scientific literacy when evaluating students' levels of scientific literacy. This was research and development using the ADDIE model. The stages of the ADDIE model are analysis, design, development, implementation, and evaluation. To gather information on the trial's empirical validity and reliability, a total of 26 students participated. The outcome demonstrates that 21 instrument items were reliable in the high category with a coefficient value of 0.89 and valid with r > 0.388. This implies that assessment instrument can be used to assess students' scientific literacy.